Lipotoxicity-induced circGlis3 impairs beta cell function and is transmitted by exosomes to promote islet endothelial cell dysfunction - Xiong, Li; Chen, Li; Wu, Liting; He, Weiman; Chen, Dubo; Peng, Zishan; Li, Jin; Zhu, Xiaonan; Su, Lei; Li, Yanbing; Gong, Yingying; Xiao, Haipeng (Diabetologia, 2022)
Aims/hypothesis Lipotoxicity constitutes the major driving force for type 2 diabetes. Circular RNAs (circRNAs) play important roles in regulating beta cell function and exosomes are essential mediators of intercellular communication. The role of exosomal circRNAs in type 2 diabetes remains largely unknown. We aimed to examine whether lipotoxicity induces dysregulation of circRNAs in beta cell-derived exosomes and to determine the contribution of exosomal circRNAs to the development of type 2 diabetes. Methods Exosomes were extracted from MIN6 cells treated with palmitate or BSA, and RNA sequencing was performed. CircGlis3 (Gli-similar 3) expression level was validated by qPCR. The impact of circGlis3 on beta cell function and the deleterious effects of exosomal circGlis3 on islet endothelial cells (islet ECs) were investigated in vitro and in vivo in human and mouse models by gain or loss of function assays. The molecular mechanism of circGlis3 was explored by RNA pull-down and immunoprecipitation assays. Results Beta cell-derived exosomal circGlis3 was significantly upregulated under lipotoxic conditions, and exosomal circGlis3 levels were also elevated in the serum of mouse models of diabetes and participants with type 2 diabetes. CircGlis3 participated in lipotoxicity-induced beta cell dysfunction in vitro and in vivo. Moreover, beta cell-derived exosomal circGlis3 could be transferred to islet ECs and reduce the cell viability, cell migration and angiogenesis of islet ECs. Mechanistically, circGlis3 promoted the degradation of glucocorticoid modulatory element-binding protein 1 (GMEB1) by facilitating the interaction between GMEB1 and mindbomb E3 ubiquitin protein ligase 2 (MIB2), thus suppressing the phosphorylation of heat shock protein 27 (HSP27). Conclusions/interpretation Our study points to the involvement of circGlis3 in diabetes development, and exosomal circGlis3 transfer as a communication mode between beta cells and islet ECs, suggesting that circGlis3 might be a potential biomarker and therapeutic target for type 2 diabetes. Data availability The RNA-sequencing data have been deposited in the NCBI Sequence Read Archive (SRA) database, with accession number PRJNA689673. Mass spectrometry data are available via ProteomeXchange with identifier PXD024693. Graphical abstract